Analisis Penggunaan Modul Digital dalam Pembelajaran Ilmu Pengetahuan Alam di SMP/MTs Kabupaten Jepara - Indana Syarifah; Ulya Fawaida; Sulasfiana Alfi Raida (Jurnal Kajian Pendidikan IPA, 2026)
The use of digital modules in Natural Science (IPA) learning in junior high schools (SMP/MTs) in Jepara Regency is the focus of a comprehensive analysis to analyze the use of digital modules focusing on usage patterns, level of effectiveness, and implementation constraints. This study aims to provide a holistic picture of the contribution of digital modules to the quality of science learning through student perceptions. A descriptive quantitative method was applied by distributing structured questionnaires to 100 students from several schools. Descriptive statistical analysis and data triangulation were used to validate the findings. The results showed an intensive usage pattern, integrating independent access outside the classroom with structured use in the classroom, supported by interactive features that increase engagement and conceptual understanding. Digital modules proved effective in terms of ease of navigation, material relevance, and flexibility of learning time. However, their implementation is still hampered by internet network instability, limited student devices, and low teacher digital competency. The conclusion of this study states that digital modules are an adaptive and effective medium, with recommendations for strengthening infrastructure, equalizing access, and ongoing training for educators and students.